2020
DOI: 10.37989/gumussagbil.734808
|View full text |Cite
|
Sign up to set email alerts
|

Toplumsal Cinsiyet Eşitsizliğinin Hemşirelik Mesleğine Yansımaları

Abstract: Bu derleme çalışmasında, toplumsal cinsiyet eşitsizliğinin hemşirelik mesleğine yansımalarının ele alınması amaçlanmıştır. Toplumun bireylere yıllardır kadın ya da erkek olarak yüklemiş olduğu roller, sorumluluklar, tutumlar ve davranışlar toplumsal cinsiyet eşitsizliğinin temelini oluşturmaktadır. Günlük yaşantımızı, aile içi rollerimizi, eğitim ve çalışma hayatımız başta olmak üzere tüm yaşantımızı etkisi altına alan toplumsal cinsiyet kavramı aslında sosyal, kültürel ve öğrenilen bir kavramdır. Ulusal ve ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 16 publications
0
1
1
1
Order By: Relevance
“…Regarding the variable of father's education level, no significant difference was observed in the gender role attitudes of students in the 1st and 4th grades of the Preschool and Primary School Teaching Program. Some research studies conducted with university students have found findings that support the findings of this research (Aylaz et al, 2014;Dinç and Çalışkan, 2016;Güzel, 2016). On the other hand, some studies do not align with this finding.…”
Section: Discussioncontrasting
confidence: 58%
“…Regarding the variable of father's education level, no significant difference was observed in the gender role attitudes of students in the 1st and 4th grades of the Preschool and Primary School Teaching Program. Some research studies conducted with university students have found findings that support the findings of this research (Aylaz et al, 2014;Dinç and Çalışkan, 2016;Güzel, 2016). On the other hand, some studies do not align with this finding.…”
Section: Discussioncontrasting
confidence: 58%
“…Aynı zamanda öğrencilerin büyük şehirde, ulaşımın kolay olduğu ya da üniversitenin bulunduğu şehrin yaşanabilir olmasından dolayı, bölüm tercih etmesinden kaynaklı zorunluluk olarak çocuk gelişimi bölümünü seçmiş olduğu düşünülebilir. (Bayram vd., 2021;Bulut ve Şahin Başfırıncı, 2021;Gönç, 2016;Ulaş vd., 2016;Zeren ve Köşgeroğlu, 2020).…”
Section: Sonuç Ve Tartışmaunclassified
“…In this context, gender roles dictate social obligations and expectations. People are born predominantly male or female, but their development within the context of gender norms is influenced by socialization [11,12].…”
Section: Main Points;mentioning
confidence: 99%